PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum .L) TERHADAP PEMBERIAN KOMPOS KULIT KOPI DAN PUPUK ORGANIK CAIR - Andi Sahputra; Asil Barus; Rosita Sipayung (Universitas Sumatera Utara, 2013)
ABSRACTShallot is one of the superior spice plants.Nowday, cultivation of shallot is directed for using inputfrom organic matter. Coffea peel compost and liquid organic fertilizer are potential nutrient sourceto use in organic cultivation of shallot. The growth and production of shallot by giving coffee barkcompost and liquid organic fertilizer. This research was proposed to find out effect of growth andproductions respons of shallot as coffee bark compost and liquid organic fertilizer. The researchstarted from october to december 2011. The design use randomized block design factorial with 2aspect. The first aspect is compost bark coffee consist of four stages those were K0 ( 0 g/plant ), K1( 30 g/plant ), K2 ( 60 g/plant ), ( 90 g/plant ). The second factor is liquid organic fertilizer consistfour stages those are P0 ( 0 ml/l water ), P1 ( 3 ml/l water ), P2 ( 6 ml/ l water ), P3 ( 9 ml/l water ).Coffee bark compost given ferform real effect to number of leave per clumb 6 MST, diameter ofbulk and production per plot but not gave any influenced to high of plant, leaves number per sample2 – 5 MST, number bulbs per sample, wet weight per sample and dry weight per sample. Liquidorganic fertilizer given ferform real effect to high of plant per sample 3 – 6 MST, leaves number persample 5 and 6 MST, diameter of bulk per sample and production per plot, but not gave anyinfluenced to high plant 2 MST, leave number per clump 2 – 4 MST, number bulbs per sample, wetweight per sample and dry weight of bulb per sample. The intraction between both aspectinfluenced on diameter of bulb.Key words : coffee bark compost, liquit organic fertilizer, shallot, growth and productions